Pengaruh Pelaksanaan Program Corporate Social Responsibility (CSR) dan Kualitas Produk Terhadap Corporate Image PT. Semen Padang (Studi Kasus Masyarakat di Kec. Lubuk Kilangan Padang) - Elsha Pratiwi, Mira; Kemala Sari, Mareta; Ramayani, Citra (Pendidikan Ekonomi, 2014)
ABSTRACT Â The background of this research background by the extent to which the implementation of Corporate Social Responsibility and affect product quality corporate image ( corporate image) PT . Semen Padang in the district. Kilangan bottom of Padang . The purpose of this study to determine whether CSR program that is given by PT . Semen Padang affect the companys corporate image . There are two benefits from this research , practical for the company , as a material consideration in implementing CSR programs . The second benefit of theoretical benefit as consideration for futureresearch .Type of research is descriptive research Associative . The population in this study overall community district. Padang Kilangan depths totaling 48 850 . Sampling using Slovin formula . Based on a formula then get a sample of 100 people . The sampling technique used is Non-Probability Sampling using samplimg acidental techniques . Data were collected through questionnaires using a Likert scale measuring devices that have been tested in the district. Begalung bottom of Padang . The data analysis technique used is descriptive analysis and analysis of Corporate Social Responsibility induktif.Program affect Corporate Image by 1,009 units . Likewise the influence Corporate Image Quality Products at 0,249 units . This can be proved by the results of research which states that the value of F ( 113.805 ) > F ( 3.936 ) . 70.1 % Corporate Image PT . Semen Padang influenced CSR Program and Product Quality while the remaining 29.9 % be explained by other factors that are outside the study .